Effects of chitooligosaccharide supplementation on laying performance, egg quality, blood biochemistry, antioxidant capacity and immunity of laying hens during the late laying period. Issue 1 (14th December 2020) - Xu, Qianqian; Azzam, Mahmoud Mostafa Mohammed; Zou, Xiaoting; Dong, Xinyang
Abstract: The effects of chitooligosaccharide (COS) supplementation in laying hen diets on egg production, egg quality, blood biochemistry, antioxidant capacity and immunity during the late laying period were investigated in this 10-week trial. A total of 3000 Fengda No.1 laying hens, 52 weeks of age, were randomly allocated to three treatment groups, each of which included five replicates of 200 hens. Treatments consisted of the basal diet only or the basal diet supplemented with COS at 75 or 125 mg/kg. Hens fed with both COS supplemented diets had improved hen-day egg production, egg mass and feed conversion ratio than control birds. The higher level of COS supplementation exerted positive effects on eggshell strength and eggshell thickness, but significantly decreased yolk colour. Addition of 125 mg/kg COS was also found to significantly increase serum albumin content and significantly decrease serum cholesterol level. Dietary supplementation with COS significantly decreased serum triglyceride level compared with birds fed the control diet. Moreover, COS significantly increased total antioxidative capacity and significantly decreased malondialdehyde level in serum, but had no significance on the activities of antioxidant enzymes. The only change in blood immune response compounds observed in this study was a significantly increased concentration of C3 when laying hens were fed COS supplemented diets. In conclusion, COS could improve laying performance and egg quality in hens during the late laying period. Inclusion of COS in the diet might be beneficial to hens' health by lowering serum lipids, enhancing antioxidant activity and slightly enhancing immune ability. HIGHLIGHTS: COS improved laying performance and egg quality in hens during the late laying period. Inclusion of COS in the diet might be beneficial to hens' health by lowering serum lipids, enhancing the antioxidant activity and slightly enhancing immune ability. The optimum concentration of COS is 75 mg/kg in the basal diet in order to achieve an increased egg production, egg quality and health condition.